2019
DOI: 10.1096/fj.201801067rr
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of class IIa histone deacetylases alleviates renal fibrosis

Abstract: In this study, we examined the effect of MC1568, a selective class IIa histone deacetylase (HDAC) inhibitor, on the development and progression of renal fibrosis in a murine model of renal fibrosis induced by unilateral ureteral obstruction (UUO). All 4 class IIa HDAC isoforms, in particular HDAC4, were up‐regulated in renal epithelial cells of the injured kidney. Administration of MC1568 immediately after UUO injury reduced expression of α–smooth muscle actin (α‐SMA), fibronectin, and collagen 1. MC1568 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 61 publications
7
46
0
Order By: Relevance
“…Noticeably, HDAC2 could bind to different loci on chromosome 11 and can modulate MMP27 bidirectionally. Previous studies suggested that the HDAC family could regulate multiple MMPs, including MMP1, MMP2, MMP3, MMP7, MMP9, MMP10, MMP13, MMP14, and MMP28, 23‐28 and that MMP10 could be regulated by HDAC3 and HDAC7 28,29 . For the first time, we found that HDAC2 could potentially modulate the MMP10, MMP16, MMP21, MMP25‐AS1, MMP27, and CD16 genes in neutrophils of AIS patients.…”
Section: Discussionmentioning
confidence: 55%
“…Noticeably, HDAC2 could bind to different loci on chromosome 11 and can modulate MMP27 bidirectionally. Previous studies suggested that the HDAC family could regulate multiple MMPs, including MMP1, MMP2, MMP3, MMP7, MMP9, MMP10, MMP13, MMP14, and MMP28, 23‐28 and that MMP10 could be regulated by HDAC3 and HDAC7 28,29 . For the first time, we found that HDAC2 could potentially modulate the MMP10, MMP16, MMP21, MMP25‐AS1, MMP27, and CD16 genes in neutrophils of AIS patients.…”
Section: Discussionmentioning
confidence: 55%
“…Noticeably, HDAC2 could bind to different loci on chromosome 11 and can modulate MMP27 bidirectionally. Previous studies suggested that the HDAC family could regulate multiple MMPs, including MMP1, MMP2, MMP3, MMP7, MMP9, MMP10, MMP13, MMP14, and MMP28 [20][21][22][23][24][25], and that MMP10 could be regulated by HDAC3 and HDAC7 [25,26]. For the first time, we found that HDAC2 could potentially modulate the MMP10, MMP16, MMP21, MMP25-AS1, and MMP27 genes in neutrophils of AIS patients.…”
Section: Discussionmentioning
confidence: 60%
“…Renal fibrosis develops in response to a host of insults such as growth factors and stress molecules, and the development goes through several important phases, including activation of renal interstitial fibroblasts, excessive and progressive accumulation of extracellular matrix (ECM) [22], EMT [23], inflammatory cell infiltration and tubular cell apoptosis [24]. During the chronic injury that occurs in CKD, continuous fibrotic matrix deposition will disrupt organ structure, suppress blood supply, affect organ function, and ultimately cause kidney failure [25,26].…”
Section: Discussionmentioning
confidence: 99%